Penerapan Evaluasi Manajemen Mutu Terpadu Pendidikan di MTs N 2 Mandailing Natal - Reni Septrisia; Dandi Dandi; Nur Habibah; Nurul Mutiah; Suhdiansah Suhdiansah; Indah Herawati Gea (Universitas Maritim AMNI Semarang, 2024)
This research aims to describe of explain the implementation of integrated education quality management evaluation at MTs N 2 Mandailing Natal. This research uses a descriptive method with a qualitative approach. The main respondent in this research was the Deputy Head of Madrasah Mts N 2 Mandailing Natal for Student Affairs. Data was collected through observation, interviews and documentation, including the use of madrasah social media to find additional sources of information. Evaluation of integrated education quality management is a systematic process that aims to ensure that all aspects of educational institutions run in accordance wint established quality standards. The evaluation carried out at MTs N 2 Mandailing Natal was fomative and summative and based on eight national education standards consisting of; student evaluation, teaching staff evaluation, and infrastructure evaluation, and curriculum evaluation. Evaluations are carried out periodically and in accordance with each main task and function, which means there are no obstacles in impementing the integrated education quality management evaluation process at MTs N 2 Mandailing Natal.